2021
DOI: 10.1097/gco.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall endometriosis: an update in diagnosis, perioperative considerations and management

Abstract: Purpose of review Abdominal wall endometriosis (AWE) is rare with limited evidence guiding diagnosis and treatment. The purpose of this review is to provide an update of the diagnosis, perioperative considerations, and treatment of AWE. Recent findings Recent studies further characterize presenting symptoms and locations of AWE. Prior abdominal surgery remains the greatest risk factor for the development of AWE. Newer evidence suggests that increasing B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…This study indicates that laparoscopic surgery for AWE has the advantages of simultaneous diagnosis and treatment of other pelvic lesions. In our study, 87.5% (7/8) of patients with AWE were found to have concomitant pelvic endometriosis during surgery, which is consistent with previous studies [ 4 , 6 , 10 , 17 ]. In traditional laparotomy for AWE, it is not necessary to routinely open the abdominal cavity if the AWE lesion is located in the subcutaneous or muscular layer of the abdominal wall and is not involved with the peritoneum; therefore, concomitant pelvic endometriosis and other lesions within the abdominal cavity cannot be diagnosed or treated simultaneously.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study indicates that laparoscopic surgery for AWE has the advantages of simultaneous diagnosis and treatment of other pelvic lesions. In our study, 87.5% (7/8) of patients with AWE were found to have concomitant pelvic endometriosis during surgery, which is consistent with previous studies [ 4 , 6 , 10 , 17 ]. In traditional laparotomy for AWE, it is not necessary to routinely open the abdominal cavity if the AWE lesion is located in the subcutaneous or muscular layer of the abdominal wall and is not involved with the peritoneum; therefore, concomitant pelvic endometriosis and other lesions within the abdominal cavity cannot be diagnosed or treated simultaneously.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that laparoscopic surgery for AWE is safe, effective and feasible and could be considered a treatment option for AWE. Laparotomic resection of AWE lesions is the first-line treatment for AWE [ 3 , 10 ]. Previous studies have shown a success rate of >95% and a postoperative recurrence rate of 1.5–11.4% for laparotomic wide local resection of AWE lesions with at least 1 cm negative margins; however, wide local resection may lead to complications such as incision infection, delayed healing, and incisional hernia [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations